Prognostic value of inflammatory markers for all-cause mortality in patients with acute myocardial infarction in the coronary care unit: a retrospective study based on MIMIC-IV database - Cao, Fen; Jiang, Jun-jun; Zhang, Gui; Liu, Jun; Xiao, Ping; Tian, Yang; Zhang, Wei; Zhang, Sheng; Hou, Feng; Bao, Zhong-Wu; Wu, Kun; Zhu, Yong-zhi (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAcute myocardial infarction (AMI) is prevalent and perilous, leading to mortality and disability in the coronary care unit (CCU). This paper was to verify the correlation of neutrophil-to-lymphocyte ratio (NLR), systemic immune-inflammation index (SII), platelet-to-lymphocyte ratio (PLR), and systemic inflammation response index (SIRI) with all-cause mortality for AMI patients in the CCU.MethodsAdult patients diagnosed with AMI and admitted to CCU were selected from the MIMIC-IV database. Various clinical and laboratory data were extracted. Logistic regression models were employed to determine the correlation between NLR and in-hospital mortality, 30-day mortality, and 90-day mortality. Confounding factors were adjusted to validate the result robustness. Restricted cubic spline (RCS) curves were adopted to analyze the potential correlation between NLR and all-cause mortality. Meanwhile, the area under the receiver operating characteristic (ROC) curve (AUC) was utilized to compare the prediction ability of NLR, SII, PLR, and SIRI in all-cause mortality. Subsequently, subgroup analyses of gender and comorbidities were performed.Results1,386 AMI patients in the CCU were enrolled. The NLR was non-linearly and positively associated with in-hospital mortality [Q4: OR (95%CI) 2.61; (1.261–5.626), p = 0.012], 30-day mortality [Q4: OR (95%CI) 2.005; (1.048–3.925); p = 0.038], 90-day mortality [Q4: OR (95%CI) 2.191; (1.235–3.948); p = 0.008] with Q1 as the reference group. The NLR had the highest AUC for in-hospital mortality, 30-day mortality, and 90-day mortality among four inflammatory markers (NLR, SII, PLR, SIRI). Stratified analyses based on gender and comorbidities showed that the risk of death was significantly increased in male and female patients, with or without diabetes, without cerebral infarction, chronic obstructive pulmonary disease, liver disease, and renal disease in the Q4 group when compared to the Q1 group.ConclusionsNLR is nonlinearly and positively associated with all-cause mortality of AMI patients in the CCU. The predictive ability of NLR in in-hospital mortality, 30-day mortality, and 90-day mortality is superior to that of SII, PLR, and SIRI.